Processing of Etawa Goat Milk into High Calcium Powder in Lerek Gombengsari Banyuwangi Educational Tourism Village - Ayu Purwaningtyas; Hani Arina Silmi; Melandia Yuliantari (Universitas Lancang Kuning, 2023)
Gombengsari has been known as a livestock center for dozens of years. They use their milk to be milked and sold. However, for now, the people around Lerek Gombengsari Tourism Village (Lego) are more focused on coffee, while many consumers of goat's milk are starting to need it. Milk that is marketed is still in the form of liquid milk which basically spoils quickly when the temperature is unstable which makes the bacteria in the milk develop faster. Based on the problems described above, the innovation of processing Etawa goat milk into powder is the solution we offer. Besides milk being able to last longer than liquid milk, it is also to facilitate delivery to consumers both within the city and outside the city. The aim is to increase the productivity of Etawa goat milk by implementing liquid milk processing into powder and promoting to the general public that Gombengsari Village can produce powdered Etawa goat milk products. With this, it is hoped that the Etawa goat milk powder typical of the Lerek Gombengsari Tourism Village can develop and be known by all local and international communities.